LITERATURE REVIEW : Kinesiology Tape Method Untuk Meningkatkan Kemampuan Fungsional Pada Kasus Osteoarthritis Lutut - Suci Amara Binashrava, (2020)
Objective: Decreased functional ability of a person is influenced by increasing age, especially in cases of knee osteoarthritis which usually occurs at the age of 45-65 years with the elderly category. Writing this review literature aims to analyze the kinesiology tape method to improve functional ability in cases of knee osteoarthritis. Methods: The method for writing a literature review is a traditional literature review, which is a comprehensive, critical, and objective analysis of knowledge related to a particular topic, which helps in identifying gaps in a science or knowledge. The search for data sources at this writing was obtained from literature studies that have been published through electronic databases such as Google Scholar, PubMed, Science Direct, Sci-Hub, and various other journal sites as well as books and other written data related to the title of this research. to evaluate the quality of selected journals or articles using the Scimago Journal & Country Rank (SJR). Results: After analyzing the literature on 5 articles, it was shown that kinesio taping was effective in significantly increasing the functional ability of knee osteoarthritis. Conclusion: Kinesio taping can improve functional ability in knee osteoarthritis.